2021
DOI: 10.1016/j.immuni.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Kupffer cell subset capable of reverting the T cell dysfunction induced by hepatocellular priming

Abstract: Highlights d KCs are required for in vivo reinvigoration of intrahepatically primed T cells by IL-2 d KCs respond to IL-2 and cross-present hepatocellular Ags d Single-cell RNA-seq identifies two distinct populations of KCs d KC2s have enriched IL-2 sensing machinery and Ag presentation capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 55 publications
4
71
0
1
Order By: Relevance
“…This analysis identified one subset of KCs. However, 2 subpopulations termed KC1 and KC2 have recently been described ( Blériot et al., 2021 ; Simone et al., 2021 ). As our CITE-seq analysis identified that the markers used to identify KC2s, namely CD206 and ESAM, are largely expressed by liver sinusoidal endothelial cells (LSECs) ( Figure S2 E), we next sought to determine if we had previously removed any potential KC2s in our initial QC steps as LSEC-KC doublets.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis identified one subset of KCs. However, 2 subpopulations termed KC1 and KC2 have recently been described ( Blériot et al., 2021 ; Simone et al., 2021 ). As our CITE-seq analysis identified that the markers used to identify KC2s, namely CD206 and ESAM, are largely expressed by liver sinusoidal endothelial cells (LSECs) ( Figure S2 E), we next sought to determine if we had previously removed any potential KC2s in our initial QC steps as LSEC-KC doublets.…”
Section: Resultsmentioning
confidence: 99%
“…[10] In other pathological conditions, KCs seem to induce a more tolerogenic differentiation of CD8 + T cells in a major histocompatibility complex (MHC)-I-dependent manner upon IL-2 stimulation. [11] Whereas the role of KCs and monocytes in NASH have been widely investigated in particular for their fibrogenic role through TGFβdependent signaling with HSCs, their interaction with T-and B-lymphocytes in promoting tumor progression seems to be etiology dependent and, possibly, associated with their polarization. [12] For instance, an elegant recent study showed that in HBV-related HCC, M2-polarized tumor-associated macrophages can promote an immunosuppressive microenvironment characterized by increased expression levels of PDCD1 (programmed cell death 1; PD1) and Tcell immunoreceptor with Ig and ITIM domains (TIGIT) on CD8 + T cells and natural killer cells.…”
Section: Inter Action Of Innate Immune and Adapti Ve Immune Cells In ...mentioning
confidence: 99%
“…While the literature describes a clear role for the RES-mediated removal of viral particles from circulation and importance in controlling viral pathogenesis, only a handful of studies have delved deeper to examine immunological responses elicited in specific RES cell populations following viral vascular clearance and the fate of captured virions [ 23 , 52 , 53 , 56 , 57 , 186 , 205 ].…”
Section: Discussionmentioning
confidence: 99%
“…While KCs are generally skewed to promote a tolerogenic T-cell response [ 202 ], they can also induce an antiviral T-cell response analogous to that observed in the secondary lymphoid organs [ 203 , 204 ]. Specifically, KC-targeted uptake of virus has been shown to produce robust, effective CTL responses [ 203 , 205 ], even in the absence of hepatic DCs [ 203 ].…”
Section: The Blood-filtering Organsmentioning
confidence: 99%